(untitled) (Лучшие интеллектуальные исследования, 2025)
Аннотация. В статье рассматривается урок-семинар как одна из действенных форм организации учебного процесса при изучении современной литературы в школе. Автор анализирует педагогические возможности семинарской формы, её влияние на развитие критического мышления, речевой культуры и читательской компетентности учащихся. Особое внимание уделяется методике подготовки и проведения семинаров, выбору актуальных литературных текстов, а также созданию условий для активного включения школьников в обсуждение нравственных, социальных и культурных проблем, затронутых в произведениях современных авторов. Abstract. The article examines the seminar lesson as one of the most effective forms of organizing the educational process in studying contemporary literature at school. The author analyzes the pedagogical potential of the seminar format and its impact on the development of students’ critical thinking, speech culture, and reading competence. Special attention is given to the methodology of preparing and conducting seminars, selecting relevant literary texts, and creating conditions for the active involvement of students in discussing moral, social, and cultural issues reflected in the works of contemporary authors.